Investigation of Novel Circuits Involved in Virgin Female Receptivity of Drosophila melanogaster - Herrmann, Dennis (2016)
Courtship is a behavior that allows the display of fitness of one sex to the other and gates possible subsequent mating. This behavior is crucial for reproduction and has strong innate components in all animals. Courtship in Drosophila melanogaster consists of a series of highly stereotyped actions that the male performs towards the female. He sings with vibrations of the wings, touches and licks her abdomen, while she evaluates the information presented to her.(...)